The detectability of radio emission from exoplanets - Lynch, Christene; Murphy, T.; Lenc, E.; Kaplan, D. (Oxford University Press, 2018)
Like the magnetized planets in our Solar system, magnetized exoplanets should emit strongly at radio wavelengths. Radio emission directly traces the planetary magnetic fields and radio detections can place constraints on the physical parameters of these features. Large comparative studies of predicted radio emission characteristics for the known population of exoplanets help to identify what physical parameters could be the key for producing bright, observable radio emission. Since the last comparative study, many thousands of exoplanets have been discovered. We report new estimates for the radio flux densities and maximum emission frequencies for the current population of known exoplanets orbiting pre-main-sequence and main-sequence stars with spectral types F-M. The set of exoplanets predicted to produce observable radio emission are Hot Jupiters orbiting young stars. The youth of these systems predicts strong stellar magnetic fields and/or dense winds, which are the key for producing bright, observable radio emission. We use a new all-sky circular polarization Murchison Widefield Array survey to place sensitive limits on 200MHz emission from exoplanets, with 3s values ranging from 4.0 to 45.0mJy. Using a targeted Giant Metrewave Radio Telescope observing campaign, we also report a 3s upper limit of 4.5mJy on the radio emission from V830 Tau b, the first Hot Jupiter to be discovered orbiting a pre-main-sequence star. Our limit is the first to be reported for the low-frequency radio emission from this source.